2021
DOI: 10.1530/erc-21-0040
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genomic analysis of 364 adrenocortical carcinomas

Abstract: Despite recent advances in elucidating molecular pathways underlying adrenocortical carcinoma (ACC), this orphan malignancy is associated with poor survival. Identification of targetable genomic alterations is critical to improve outcomes. The objective of this study was to characterize the genomic profile of a large cohort of patient ACC samples to identify actionable genomic alterations. Three hundred sixty-four individual patient ACC tumors were analyzed. The median age of the cohort was 52 years and 60.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…The application of MMR proteins (MLH1, MSH2, MSH6 and PMS2) has gained popularity not only for the purpose of screening for an extracolonic manifestation of Lynch syndrome [18,179,180] (Fig. 36), but also to provide additional guidance on the use of immunotherapy trials [4,181]. Similarly, the PDL1/ PD1 expression status of ACCs has been an area of interest.…”
Section: Question 10: Which Ancillary Tools Should Pathologists Consi...mentioning
confidence: 99%
“…The application of MMR proteins (MLH1, MSH2, MSH6 and PMS2) has gained popularity not only for the purpose of screening for an extracolonic manifestation of Lynch syndrome [18,179,180] (Fig. 36), but also to provide additional guidance on the use of immunotherapy trials [4,181]. Similarly, the PDL1/ PD1 expression status of ACCs has been an area of interest.…”
Section: Question 10: Which Ancillary Tools Should Pathologists Consi...mentioning
confidence: 99%
“…Although more than half of ACCs have one or more potentially actionable genomic alterations, results of nextgeneration sequencing or other methods to assess ACC for personalized approaches revealed that the vast majority of DNA alterations detected are not druggable by molecular target agents currently available in the treatment of solid tumors results. 35,36 In the current single-institution, nonrandomized phase II study, cabazitaxel showed a disease control rate after 4 months of 24%. Therefore, formally we could not conclude that this drug is not efficacious in the management of chemotherapy pretreated advanced ACC patients, according to the predefined limits that we have fixed to calculate the sample size of this trial.…”
Section: Discussionmentioning
confidence: 88%
“…Although more than half of ACCs have one or more potentially actionable genomic alterations, results of next-generation sequencing or other methods to assess ACC for personalized approaches revealed that the vast majority of DNA alterations detected are not druggable by molecular target agents currently available in the treatment of solid tumors results. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…CTNNB1 was altered in 14.8% of the TCGA samples and 28% of the foundation one tumors [ 14 ]. Interestingly, it was more frequently altered in metastatic ACC, as opposed to localized stages ( Figure 2 ), suggesting that CTNNB1 could be involved in the switch to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-catenin seems to play a major role in both localized and advanced or metastatic ACC, which additionally displays ERBB4, GPCR, RAR, and PDGFR as further possible targets [ 9 ]. However, in spite of a recent study suggesting that more than a half of 364 ACC tumors may show actionable mutations based on OncoKB [ 10 ], clinical studies testing drugs that target the vascular endothelial growth factor (VEGF) pathway [ 11 ], the epidermal growth factor receptor (EGFR) pathway [ 12 , 13 ], the insulin-like growth factor 1 receptor (IGF-IR) pathway [ 14 ] or the mammalian target of rapamycin (mTOR) pathway [ 15 , 16 ] were discouraging so far [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%